Is boophilus microplus the main vector of anaplasma marginale? Technical note - Coronado, Alfredo (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
Understanding of Anaplasma marginale epidemiology demands the evaluation of several factors, involving not only biological or mechanical vectors, but also physiological events such as host immunity, intrauterine infection of fetus and parasite behavior in the host. The actual role that the one-host tick Boophilus microplus plays in the transmission of the ehrlichial A. marginale seems to be less important than previously thought. Â